The efficacy of clopidogrel in preventing recurrent cardiovascular events among Arab population carrying different CYP2C19 mutations: systematic review and meta-analysis - Abdullah N. Alkattan; Nashwa M. Radwan; Nagla E. Mahmoud; Amjad F. Alfaleh; Amal H. Alfaifi; Khaled I. Alabdulkareem (Egyptian Journal of Medical Human Genetics, 2022)
Abstract Background The prevalence and the role of CYP2C19 gene mutations concerning recurrent Cardiovascular Events (CVEs) among patients treated with clopidogrel is still controversial especially among Arab people. Therefore, this review aimed to determine the frequency of CYP2C19 polymorphic alleles among the Arab population and to investigate the efficacy of clopidogrel as an antiplatelet drug among those carrying different variants of this gene. Methodology Two authors independently searched in PubMed, Google Scholar, and EMBASE databases at any year for studies related to the role of CYP2C19 gene on the prognosis of patients with CVEs treated with clopidogrel. The review included Arab people who were genotyped to determine the frequency of CYP2C19 genotypes and alleles (the qualitative part). Concerning the quantitative part (meta-analysis), only patients who previously had CVEs and using clopidogrel as secondary prophylaxis had been included. The Newcastle Ottawa Scale for non-randomizes Studies was utilized to consider the risk of bias among included studies. We analyzed the data using odds ratio at 95% confidence interval and the quality of evidence of each outcome measure was judged using GRADE approach. Results The current study revealed that 4% of Arabs reported in the included studies are homozygous, and 25% are heterozygous for the CYP2C19*2 allele. While 3% and 18.5% of them are homozygous and heterozygous of CYP2C19*17 alleles, respectively. A significant increased risk of recurrent CVEs by about threefold was associated with CYP2C19*2 or CYP2C19*3 allele carriers (OR = 3.32, CI = 1.94–5.67, and OR = 3.53, CI = 1.17–10.63, respectively). However, no significant increased risk among carriers of CYP2C19*17 mutation (OR = 0.80, (CI = 0.44–1.44) was documented. Conclusion The present study revealed that Arabs carrying CYP2C19*2 and CYP2C19*3 alleles could be at increased risk of decreasing the antiplatelet efficacy of clopidogrel and an alternative drug should be prescribed for those patients to avoid recurrent CVEs. However, few available studies were included in the quantitative part of the analysis and further studies with large sample size are recommended to confirm our results.